Analysis of Students' Perception Toward the Use of the Fondi Application to Learn Speaking English in Junior High School - Arifiyana, Athiyah; Dzulfikri (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
This study aims to determine students’ perceptions of using the FONDI application for speaking practice and the research uses the Fondi application because this application is still rarely used for classroom learning. The design of this research was descriptive qualitative. Data collection using interviews with students of Junior High School in Banyuwangi. Five students who had been using the FONDI application for around two months were interviewed, such that while using the FONDI program for speaking practice, these students may describe their perceptions, improving the quality and fluidity of their speaking. After conducting interviews, the results showed that students gave positive perceptions, such as, the students feeling happy, enthusiastic, and increasingly eager to use the Fondi application to improve their speaking skills. But students also gave negative perceptions, such as,  that Fondi should be subscribed at a cost that is quite expensive and should be supported by the internet.